WETLAND FIRE DISASTER MANAGEMENT EFFORTS: ECOSYSTEM PROTECTION AND CARBON STORAGE - Jannah, Miftahul (International Conference On Social Science Education, 2023)
This article discusses efforts to overcome fire disasters in wetlands with a focus on ecosystem protection and carbon storage. Wetlands, as important ecosystems with a vital role in maintaining biodiversity and regulating the water cycle, are vulnerable to fire risks which can threaten natural sustainability and carbon storage. This research uses a descriptive qualitative approach with literature study as a data collection technique originating from scientific journals, books and other literature that is appropriate to the topic of discussion. This discussion resulted in a fire management strategy in wetlands that involves preventing, monitoring, and responding quickly to fire threats through public education, water management, and the use of advanced technology with inter-agency collaboration, involving the government and local communities in efforts to prevent and manage fire disasters. Where ecosystem protection in wetlands also has an impact on carbon storage. Fires can release carbon that has been stored in soil and vegetation, contributing to greenhouse gas emissions and climate change. Therefore, good management of wetlands as a natural resource not only mitigates the risk of fire, and the negative impacts of climate change but also plays a role in maintaining carbon reserves which are important for global ecological balance.